DESAIN DAN UJI COBA MEDIA MACROMEDIA FLASH BERBASIS PROBLEM BASED LEARNING PADA MATERI HIDROKARBON - Novia Hidayati; yuni fatisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research was instigated by Chemistry subject that only had concepts, it did not connect the concepts to daily life. This research aimed at knowing designing and testing Problem Based Learning based Macromedia Flash media on Hydrocarbon lesson and knowing the levels of validity and practicality of Problem Based Learning based Macromedia Flash media. It was a Research and Development (R&D) with Borg and Gall development model. It was administered at Islamic Integrated Senior High School of Al-Ittihad Pekanbaru. The subjects of this research were material experts, media experts, Chemistry subject teachers, and the eleventh-grade students of Natural Science. The object was Problem Based Learning based Macromedia Flash media on Hydrocarbon lesson. Media could be proper, if it was valid and practical. Validity percentage obtained from material experts was 93.30% (very valid), validity percentage obtained from media experts was 96% (very valid), practicality percentage obtained from chemistry subject teachers was 84.60% (very practical), and 84% students responded very well to overall design of Macromedia Flash media. Based on these results, it could be identified that Problem Based Learning based Macromedia Flash media could be implemented in the next stage. Keywords: Macromedia Flash Media, Problem Based Learning, Hydrocarbon